National assessment of extreme sea-level driven inundation under rising sea levels - Paulik, Ryan; Wild, Alec; Stephens, Scott; Welsh, Rebecca; Wadhwa, Sanjay (Frontiers in Environmental Science, 2023)
Episodic inundation from extreme sea-levels (ESLs) will have increasing social and economic impacts in response to relative sea level rise (RSLR). Despite the improved global understanding of ESL frequencies and magnitudes, detailed nationwide inundation maps are unavailable for many countries. This study quantifies New Zealand’s land area exposure to inundation from ESLs and RSLR by: (i) calculating ESL heights for nine annual recurrence intervals (ARI) between 2 and 1000-years, (ii) converted into space-varying water surface grids, (iii) developing a composite topographical dataset comprised of Airborne Light Detection and Ranging (LIDAR) and bias corrected Shuttle Radar Topography Mission (SRTM), (iv) modifying topographical data to represent mitigation structures, and (v) executing a scalable static model to map land inundation areas for 0.1 m RSLR increments. This modular approach supports continuous integration of new models and data at resolutions appropriate for quantifying inundation hazard and risk trends. In response to 0.1 m to 0.4 m RSLR expected in the New Zealand region from 2040 and 2070 under SSP5-8.5 global mean sea level rise scenarios, a rapid cumulative inundation area increase is observed for 10 and 100-year ESL ARIs at national and regional levels. The RSLR time independent maps developed here supports future investigations of ESL inundation hazards and risks for any prescribed RSLR heights or timeframes.